Der Beamtenapparat auf den kaiserlichen Herrschaften Holíč und Šaštín in der zweiten Hälfte des 18. Jahrhunderts - Fialová, Ivana (Theatrum historiae, 2012)
The study deals with the mode of operation of the imperial estates of Holíč and Šaštín in the second half of the 18th century. It focuses on the composition of the administration of both the estates and details individual clerks's competences, their duties as well as their rewards for their service.